Chondroprotective effects of alpha-lipoic acid in a rat model of osteoarthritis. (2nd July 2016) - Wang, Ji; Sun, Huijun; Fu, Zhuodong; Liu, Mozhen
ABSTRACT: Objective: The purpose of this study was to investigate whether alpha-lipoic acid (ALA) confers a chondroprotective effect on articular cartilage in rats with monosodium iodoacetate (MIA)-induced osteoarthritis (OA). Methods: Fifty male SD rats were divided into five groups, including SHAM-operated, MIA-induced OA, and three experimental groups treated with 50-, 100-, or 200-mg/kg ALA. After 14 d of ALA treatment, rats were sacrificed for joint macroscopic and histology assessments. The gene and protein expressions of markers related to chondrocyte phenotype, caspase proteins, NADPH oxidase 4 (Nox4), p22 phox, activation of nuclear factor-κB (NF-κB), and endoplasmic reticulum (ER) stress were measured by Western blot analyses or qRT-PCR. Results: The results showed that MIA injection successfully induced OA by causing cartilage degeneration. Morphological and histological examinations demonstrated that ALA treatment, especially 200 mg/kg of ALA, significantly ameliorated cartilage degeneration in rats with MIA-induced OA. ALA could effectively increase the levels of the collagen type II and aggrecan genes and inhibit apoptosis-related proteins expression. ALA reduced biomakers of oxidative damage and over-expression levels of Nox4 and p22 phox . ALA also suppressed ER stress and inhibited the activation of NF-κB pathway. Moreover, ALA obviously inhibited TNF-α secretion and Wnt/β-catenin signaling way. Conclusion: These findings indicated that ALA might be a potential therapeutic agent for the protection of articular cartilage against progression of OA through inhibition of oxidative stress, ER stress, inflammatory cytokine secretion, and Wnt/β-catenin activation.